Utilizing Used Lubricants to Enhance Intermediate Crude Oil Recovery Through Water-in-Oil Emulsions - Alfatih, Mukhlis Noor; Mardiana, Dwi Atty; Riswati, Shabrina Sri; Park, Changhyup (Scientific Contributions Oil and Gas, 2025)
This study experimentally analyzes the impacts of water-in-oil (W/O) emulsion derived from used lubricants on enhanced intermediate-crude-oil recovery. The objective is to identify a viable and economically efficient method to enhance the extraction of intermediate crude oil. Typically, W/O emulsions have been employed as displacing fluids in heavy oil reservoirs. According to the results, there have been challenges experienced in the selection of an affordable petroleum-based product and ensuring its availability for emulsion preparation. Used lubricants can be incorporated as a component in the formulation of an emulsion solution by mixing them with brine. The physical and chemical properties of these used lubricants are evaluated to determine their suitability as a displacing agent. Subsequently, several concentrations of the emulsion were prepared, ranging from 5% to 60% (vol/vol), to effectively evaluate their suitability as a displacing fluid. The experimental workflow covered viscosity testing, mobility ratio measurement, IFT evaluation, emulsion stability checks, adsorption analysis, and thermal stability assessment. Core-flooding is performed to determine the recovery factor. A 5% W/O emulsion is found to be an effective displacing fluid for intermediate crude oil. The core-flooding results showes about a 27% increase in recovery when using the conventional flooding emulsion. Overall, the findings indicate that adding used lubricants to W/O emulsions improves intermediate oil recovery due to their favorable viscosity and stability.